Health services for substance use disorders: challenges and future perspectives - João Pedro Silva (BMC, 2023)
Abstract Research on the health services' response to substance use disorders and respective comorbidities holds major relevance due to the increasing prevalence of these ailments. We thus invite contributions to a new Collection of articles launched by BMC Health Services Research titled "Health services for substance use disorders".